DESIGN AND DEVELOPMENT OF PORTABLE 3-IN-1 COLLECTION TROLLEY - Mohamad, Mahmod Abd Hakim; Yahya, Mohd Shahir; Janon, Mohd Najib; Ngadimon, Khairulnizam; Ismail, Suhairi; Kadis, Ghazali; Abd Aziz, Azizul Rahman; Yap, Jacky (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2026)
The increasing volume of food waste generated in institutional dining facilities presents significant challenges in terms of operational efficiency, hygiene, and environmental sustainability. This study presents the design and development of a portable 3-in-1 collection trolley aimed at improving plate handling and food waste management in university café environments. The proposed system integrates a spring-loaded plate stacking mechanism, a dedicated utensil compartment, and an enclosed waste bin within a single mobile unit. The design adopts a systematic engineering approach, incorporating user-centered design principles, morphological analysis, and mechanical performance evaluation. Experimental validation demonstrates that the trolley can safely support up to 80 plates while maintaining stability and accessibility. In addition, the enclosed waste compartment significantly reduces odour emission and pest attraction compared to conventional open systems. User feedback further indicates improvements in operational efficiency, ergonomics, and workplace hygiene. The findings suggest that the proposed design offers a cost-effective and sustainable solution for improving food service operations, with potential applications in institutional and commercial environments.